Peranan Dinas Kebudayaan dan Pariwisata Kabupaten Lingga dalam Pengembangan Objek Wisata - Nurbaiti Usman Siam (LLDIKTI Wilayah X, 2014)
In developing the tourism potential in the area of coastal tourism, Culture and Tourism Department launched Lingga regency coastal resorts as tourist areas open to the medium, the potential developed is the beach and the sea through the attraction beach maintenance activities, and to carry out a program of cultural potential of the Tourism Village that will be working on the Daik Village, the Village and Village Mepar Resun, while the infrastructure facilities in collaboration with the private sector and other areas such devices and Sanitation Department and the Department of Public Works. Kegaiatan promotion done DinasKebudayaan and Tourism Lingga Regency done in two ways: through events and through the mass media and supported by the provincial government and the private sector which is also a hotel and culinary tourism players.Keywords: Development, Tourism, Culture